A novel bacteriocin PE-ZYB1 produced by Pediococcus pentosaceus zy-B isolated from intestine of Mimachlamys nobilis: Purification, identification and its anti-listerial action. (January 2020) - Zhang, Ying; Yang, Jingming; Liu, Ying; Wu, Yaqian; Fang, Zhijia; Wang, Yaling; Sun, Lijun; Deng, Qi; Gooneratne, Ravi; Xiao, Lixia
Abstract: A novel bacteriocin, PE-ZYB1, was produced by Pediococcus pentosaceus zy-B that was isolated from the intestine of Mimachlamys nobilis and collected from the South China Sea. The bacteriocin PE-ZYB1 was purified using acetic ether extraction, Sephadex LH-20 column chromatography, sepharose cation exchange chromatography and reversed-phase high-performance liquid chromatography (RP-HPLC), in succession. Its molecular mass was determined to be MW 2019.22 Da, and its N-terminal amino acid sequence was DLFNKFNRSMQYGNGVE. The PE-ZYB1 was confirmed as a novel bacteriocin through a homology search, using UniProt BLAST (NO. A0A1Y0VLN8). Bacteriocin PE-ZYB1 was found to have extensive spectrum antimicrobial activity against both Gram-positive and Gram-negative bacteria. Bacteriocin PE-ZYB1 showed resistance to heat, was highly stable over pH 2–7 and was sensitive to trypsin. Increased extracellular electrical conductivity was detected for Listeria. monocytogenes treated by bacteriocin PE-ZYB1. Furthermore, bacteriocin PE-ZYB1 bactericidally destroyed the cell membrane integrity of L. monocytogenes, resulting in cell membrane perforation and permeabilization. These results indicate the potential of the bacteriocin PE-ZYB1 for use as a food bio-preservative. Highlights: A novel bacteriocin PE-ZYB1 was produced by Pediococcus pentosaceus zy-B. The molecular mass of the purified bacteriocin PE-ZYB1 was 2019.22 Da. PE-ZYB1 was confirmed as a novel bacteriocin through a homology search. Heat resistant and possess broad spectrum antimicrobial activity of PE-ZYB1. Bacteriocin PE-ZYB1 destroyed the integrity of cell membrane.